Closing the Gender Gap : Opportunities for the Women's Mobile Financial Services Market in Bangladesh - Barooah, Prabir; Sahoo, Samveet; Bhat, Sunil; George, Denny (International Finance Corporation, Washington, DC, 2018)
The report highlight the opportunities, problems, and challenges related to the financial inclusion of women through MFS adoption in Bangladesh. The data in this report was collected through a nationally representative survey of 2,000 female mobile financial services (MFS) users and 2,000 female non-users across the country.